Collective Identity Profiles: The Case of Francophones in Manitoba - Levesque, Annabel; Gueye, N’deye; Rivard, Étienne; de Moissac, Danielle; Archambault, Hélène (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2023)
This quantitative study seeks to explore collective identity profiles that emerge among French-speaking adolescents and young adults in Manitoba. A total of 493 participants completed a questionnaire measuring their level of identification with Francophone and Anglophone identities, their perception of continuity with respect to the future of the French language and culture in Manitoba, and their mental wellbeing. The results of a cluster analysis revealed four collective identity profiles, namely Bilingual Optimist, Franco-Dominant Optimist, Indifferent Pessimist, and Anglo-Dominant Pessimist. Participants who belonged to each of these profiles differed in terms of their age, their mother tongue, the type of school they attended, and their gender. Moreover, collective identity profiles were linked to participants’ mental wellbeing, with those in the Bilingual Optimist profile and those in the Franco-Dominant Optimist profile demonstrating a significantly higher level of mental wellbeing compared to the other two profiles.